Analysis of the Levels of Ethanol Extract Flavonoid Compounds in Cocor Bebek (Kalanchoe Pinnata) Leaves using UV - Vis Spectrophotometer - Tisman, Ulfana; Supriadi, Supriadi (Universitas Tadulako, 2023)
Cocor bebek is a plant that is easy to cultivate in Indonesia. This cocor bebek contains chemical compounds such as steroids, alkaloids, glycosides, tannins, and flavonoids which have antioxidant properties. Research on the analysis of flavonoid levels in the leaves of cocor bebek (kalanchoe pinnata) has been carried out using the UV-Vis spectrophotometric method. This research aims to determine the levels of flavonoids in the ethanol extract of cocor bebek leaves. The extract of chemical content in cocor bebek leaves was carried out by maceration method using 70 % ethanol. The flavonoid content of the sample extract was measured by measuring the absorption at wavelengths of 510 nm and 700 nm. The results obtained in the qualitative test showed that the cocor bebek leaf extract was positive for flavonoids which were characterized by a change in color from brownish red to green. The results of the quantitative test showed that the flavonoid content in the cocor bebek leaf extract was 0.321 mg/100 g.